Population decline in the endemic Atlantic salmon (Salmo salar) in Kapisillit River, Greenland - Hedeholm, Rasmus Berg; Broberg, Mala; Nygaard, Rasmus; Grønkjær, Peter (Fisheries management and ecology, 2018)
Atlantic salmon, Salmo salar L., is found throughout the North Atlantic, with thousands of rivers having spawning populations. In Greenland, spawning is limited to one river in West Greenland, the Kapisillit River (64˚N), and the salmon are limited to the lower few kilometres of the system. Using mark–recapture, it was estimated the parr population was 5,953 individuals, and that the population size has declined by 52% since 1959. In spite of this decline, parr density remains high, being between 0.26 and 0.62 parr/m2. Using a historical age‐length key, an estimated minimum of 635 smolt will have descended to the sea in 2017. These will be caught in a fishery currently subject to no regulatory measures and fishing remains the most likely driver of the population decline. The genetically distinct population is endemic to Greenland, and managers should implement measures to conserve this genetic integrity and local biodiversity.